Pengaruh Persentase Penambahan Mayonnaise Pada Pembuatan Sambal Mayo-Matah Terhadap Lama Penyimpanan Dan Daya Terima Konsumen Di Kitcheroo Cafe - Siti Hadiyya Yasmin; Ridawati Ridawati; Guspri Devi Artanti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
This study aims to identify the length of storage and consumer acceptance of complementary foods, namely chili sauce matah which has been given a percentage of mayonnaise as much as 10%, 20% and 30%. And this fusion food chili sauce is called mayo-matah. This research uses a quantitative approach with a survey method. This research was conducted at Kitcheroo Café. The samples of this study were 4 Culinary Education Expert Panelists and 30 Kitcheroo Cafe Customers using the data statistical analysis method, namely the Friedman test. The Friedmen test is used because the data in this study are categorical and it is more appropriate to use non-parametric statistical tests. seen all aspects (lemongrass aroma, citrus leaf aroma, creamy texture, acidity level and spiciness level) and aspects of the level of preference for consumer acceptance. The results of the validation test stated that there was an influence on the creamy texture aspect and the level of spiciness in the mayo-matah sauce which was given a percentage of mayonnaise as much as 10%, 20%, and 30%.